Implementing ASSURE Model in Islamic Religious Education to Develop 21st Century Competencie - Ihsan, Mahlil Nurul; Hartati, Mudji; Rahman, Afrillia Muthia (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2025)
This study aims to examine the implementation of the ASSURE learning design model in Islamic Religious Education (PAI) subjects to build student competencies in the 21st century. The type of research used is qualitative descriptive research with a case study approach on students in a high school. The data collection techniques used include observation, interviews, and documentation to obtain information related to the implementation of the ASSURE model in the learning process. The results show that the application of the ASSURE model can increase student engagement in learning, strengthen 21st century skills such as collaboration, creative thinking, critical, communication and digital literacy, and improve their understanding of PAI materials. Nonetheless, some challenges arise related to the availability of technological infrastructure and the time constraints to analyze student characteristics in depth. Overall, the ASSURE model has proven effective in improving the quality of PAI learning and equipping students with the competencies needed to face global challenges.